A simplified space vector modulation for the single-phase active power decoupling quasi-Z-source inverter - Rui Zhang; Shunliang Wang; Yuan Li; Junpeng Ma; Peng Wang; Tianqi Liu (International Journal of Electrical Power & Energy Systems)
The double-line frequency ripple power of the single-phase quasi-Z source inverter (qZSI) will result in a large designed qZS impedance on the dc side, which can be greatly reduced by the coupled-type active power decoupling (APD) method. However, the traditional sinusoidal pulse width modulation (SPWM) for the APD-qZSI needs extravagant APD storage capacitance and may cause abnormal operation under low load conditions. Classical space vector modulation (SVM) has higher flexibility and dc-link voltage utilization, but it cannot be directly applied to the APD-qZSI. In this paper, a simplified SVM method for the coupled-type APD-qZSI is proposed, where the switching time sequence is transformed to carrier-based pulse width modulation, so the shoot-through control of the qZSI is easy to implement. Next, the passive component parameters and normal operation range of the traditional SPWM and the proposed SVM are analyzed and compared. The proposed SVM has a smaller APD storage capacitance but a slightly larger ac side filter inductance. In addition, the decreased current of the APD branch under SVM can help suppress the abnormal operation of the inverter, so the APD-qZSI can operate at a lower load condition. Finally, experimental results validate the effectiveness and superiority of the proposed SVM method.